REVIEW OF LEGAL PROTECTION FOR CRIMINAL ACTS CHILD NARCOTICS AS DRUG DEALERS IN Law 35 of 2009 concerning Narcotics and Law no. 35 of 2014 concerning Child Protection (Study of Decision Number 7/Pid.Sus/2024/PN Mdn) - Daniel Mulia; T. Riza Zarzani; Henry Aspan (CV. RADJA PUBLIKA, 2025)
This research analysis is related to the Review of Legal Protection for Narcotics Crimes for Children as Drug Dealers in Law 35 of 2009 concerning Narcotics and Law no. 35 of 2014 concerning Child Protection (Decision Study: 7/Pid.Sus-Anak/2024/PN.Mdn. Which in this case occurred where in this case the perpetrator of a narcotics crime was a minor and committed the crime of narcotics distribution and was subject to punishment based on article 114 Paragraph 1 with a sentence of life imprisonment or a minimum of 5 years and a maximum of 20 years, the final decision in the trial was deemed by the author to not fulfill the elements of child protection by considering that the child was a victim ordered by the defendant Teguh and dropped out of 6th grade elementary school because of family economic factors and laziness in studying as regulated in Law 35 of 2014 concerning child protection the judge's decision regarding legal protection for criminal acts of child narcotics dealers based on Law No. 35 of 2009 concerning Narcotics and Law no. 35 of 2014 concerning Child Protection where by considering these two laws, children who commit criminal acts can obtain their rights and can be.